Robotic arm-assisted unicompartmental knee arthroplasty: preoperative planning and surgical technique - Roche, Martin; O'Loughlin, Padhraig F; Kendoff, Daniel; Musahl, Volker; Pearle, Andrew D (The American journal of orthopedics (Belle Mead, N.J.), 2009)
The goals of computer-assisted surgery (CAS) are to be patient-specific, minimally invasive, and quantitative. CAS can involve preoperative imaging and planning, intraoperative execution, and postoperative evaluation. Ideally, these components are integrated such that sophisticated diagnostic technologies are used to inform a patient-specific surgical plan. A recently developed CAS/robotic system has the potential to improve alignment in and results of unicompartmental knee arthroplasty. This new robot is "semiactive"; that is, the surgeon retains ultimate control of the procedure while benefiting from robotic guidance within target zones and boundaries. Surgeons who use the robotic arm-assisted technique described in this article can prepare and then precisely execute a patient-specific computed-tomography-based operative plan. The surgical field is predefined, and the active constraints used by the robotic arm eliminate inadvertent deviation outside this field, thus minimizing iatrogenic morbidity and maximizing bone preservation. In this article, we detail the preoperative planning and intraoperative technique for robotic arm-assisted unicompartmental knee arthroplasty.